Prevalence of hematologic toxicity from copperhead envenomation: an observational study. (2nd April 2020) - Wills, Brandon K.; Billet, Michael; Rose, S. Rutherfoord; Cumpston, Kirk L.; Counselman, Francis; Shaw, Kendall J.; Cresswell, Kellen G.; Charlton, Nathan
Abstract: Background: Copperhead snakes ( Agkistrodon contortrix ) are considered as the least toxic of the North American pit vipers. The reported incidence of coagulopathy from copperhead envenomation is variable, possibly secondary to regional variation in subspecies and venom potency. Coagulation studies are often obtained when evaluating for the coagulopathic effects of copperhead venom, but the clinical utility of these indices is unclear. The aim of this study was to determine the prevalence of hematologic toxicity due to copperhead envenomation in hospitalized patients. Methods: This was a multi-center retrospective chart review study using electronic hospital data between January 1, 2006 and December 31, 2016 evaluating prevalence of coagulopathy following copperhead envenomation. Patients presenting to one of three major academic tertiary care centers in Virginia with suspected copperhead envenomation were identified using medical billing codes. The primary outcome was to summarize the prevalence of hematologic toxicity including thrombocytopenia, elevated prothrombin or partial thromboplastin times, or hypofibrinogenemia. Results: There were 244 cases used for final analysis. Hematologic toxicity occurred in 14% (95% CI 10–18%) of patients. Specific indices included thrombocytopenia in 1.2% (95% CI 0.4–3.6%), hypofibrinogenemia in 0.7% (95% CI 0.0–3.8%), elevated PT in 10.0% (95% CI 6.8–14.5%), and aPTT in 3.9% (95% CI 2.1–7.2%) of patients. There was no clinically significant bleeding reported in any case. Conclusions: Subtle hematologic abnormalities due to copperhead envenomation in patients treated in the Commonwealth of Virginia were relatively common, but do not appear to be clinically significant in this study population.